Oral Immunization With a Plant HSP90-SAG1 Fusion Protein Produced in Tobacco Elicits Strong Immune Responses and Reduces Cyst Number and Clinical Signs of Toxoplasmosis in Mice - Edwin F. Sánchez-López; Mariana G. Corigliano; Sonia Oliferuk; Victor A. Ramos-Duarte; Maximiliano Rivera; Luisa F. Mendoza-Morales; Sergio O. Angel; Valeria A. Sander; Marina Clemente (Frontiers in Plant Science, 2021)
Plant 90kDa heat shock protein (HSP90) is a potent adjuvant that increases both humoral and cellular immune responses to diverse proteins and peptides. In this study, we explored whether Arabidopsis thaliana HSP90 (AtHsp81.2) can improve the immune effects of a Toxoplasma gondii surface antigen 1 (SAG1). We designed two constructs containing the sequence of mature antigen (SAG1m), from aa77 to aa322, and B- and T-cell antigenic epitope-containing SAG1HC, from aa221 to aa319 fused to AtHsp81.2 sequence. When comparing the transient expression in Nicotiana tabacum X-27-8 leaves, which overexpress the suppressor helper component protease HC-Pro-tobacco etch virus (TEV), to that in N. benthamiana leaves, co-agroinfiltrated with the suppressor p19, optimal conditions included 6-week-old N. benthamiana plants, 7-day time to harvest, Agrobacterium tumefaciens cultures with an OD600nm of 0.6 for binary vectors and LED lights. While AtHsp81.2-SAG1m fusion protein was undetectable by Western blot in any of the evaluated conditions, AtHsp81.2–SAG1HC was expressed as intact fusion protein, yielding up to 90μg/g of fresh weight. Besides, the AtHsp81.2–SAG1HC mRNA was strongly expressed compared to the endogenous Nicotiana tabacum elongation factor-alpha (NtEFα) gene, whereas the AtHsp81.2–SAG1m mRNA was almost undetectable. Finally, mice were orally immunized with AtHsp81.2–SAG1HC-infiltrated fresh leaves (plAtHsp81.2–SAG1HC group), recombinant AtHsp81.2–SAG1HC purified from infiltrated leaves (rAtHsp81.2–SAG1HC group), non-infiltrated fresh leaves (control group), or phosphate-buffered saline (PBS group). Serum samples from plAtHsp81.2–SAG1HC-immunized mice had significantly higher levels of IgGt, IgG2a, and IgG2b anti-SAG1HC antibodies than serum from rAtHsp81.2–SAG1HC, control, and PBS groups. The number of cysts per brain in the plAtHsp81.2–SAG1HC-immunized mice was significantly reduced, and the parasite load in brain tissue was also lower in this group compared with the remaining groups. In an immunoblot assay, plant-expressed AtHsp81.2-SAG1HC was shown to react with antibodies present in sera from T. gondii-infected people. Therefore, the plant expression of a T. gondii antigen fused to the non-pathogenic adjuvant and carrier plant HSP90 as formulations against T. gondii can improve the vaccine efficacy, and plant extract can be directly used for vaccination without the need to purify the protein, making this platform a suitable and powerful biotechnological system for immunogenic antigen expression against toxoplasmosis.